ASSOCIATION OF DRY EYES ON SMOKING HABITS: A SYSTEMATIC REVIEW - Lianda, Felia (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Introduction: Dry eye disease (DED), dry eye syndrome, and keratoconjunctivitis sicca (KCS) are typical reasons for eye doctor visits. Smoking's effect on DED is yet unknown, and there is conflicting evidence. Several factors contributed to this outcome, including the studies' limited sample sizes, the imbalance of components between cases and controls, and the ambiguous smoking status classification. This article shows a link between smoking and dry eye condition. The aim: This piece of writing provides evidence that demonstrates a connection between smoking and dry eye diseases. Methods: For this systematic review, publications that were published from 2013 to 2023 were taken into account during the search process. This was achieved through the utilization of numerous online reference sources, such as Pubmed and SagePub. The decision was made to exclude review articles, previously published works, and incomplete works. Result: We found 92 articles from PubMed and 107 articles from SagePub, for which title and abstract analysis was carried out. We found 23 relevant articles. We found 11 studies demonstrates a connection between smoking and dry eye diseases. Conclusion: Smoking may not cause DED. The risk of smoking and DED is still debated due to inconsistent findings.